Life Scientist Mobility from Academe to Industry: Does Academic Entrepreneurship Induce a Costly ?Brain Drain? on the Not-for-Profit Research Sector? - Andrew A. Toole; Dirk Czarnitzki (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2007)
When academic researchers participate in commercialization using for-profit firms there is a potentially costly trade-off – their time and effort are diverted away from academic knowledge creation. This is a form of brain drain on the not-for-profit research sector which may reduce knowledge accumulation and adversely impact long-run economic growth. In this paper, we examine the economic significance of the brain drain phenomenon using scientist-level panel data. We identify life scientists who start or join for-profit firms using information from the Small Business Innovation Research (SBIR) program and analyze the research performance of these scientists relative to a control group of randomly selected research peers. Combining our statistical results with data on the number of university spin-offs in the U.S. from 1994 to 2004 we find the academic brain drain has a nontrivial impact on knowledge creation in the not-forprofit research sector.
Keywords: 330; Forschungskooperation; Brain Drain; Hochschulforschung; Industrielle Forschung; Nonprofit-Organisation; Naturwissenschaftler; Arbeitsmobilität; USA